Die „Gleichzeitigkeit des Ungleichzeitigen“ als Problem transkultureller historischer Komparatistik am Beispiel frühmittelalterlicher Herrschaftslegitimation - Drews, Wolfram (Comparativ, 2008)
At nearly the same time the ruling dynasties changed both in the Frankish realm and in the Islamic caliphate around the middle of the 8th century. A detailed analysis of the religious and cultural conditions shows that rulers had to take into account the respective stages of institutionalization and canonization processes. A close comparative look at the political options open to historical contemporaries in different “cultures” or “civilizations” can make a substantial contribution towards conceptualizing transcultural historiography in global perspective.